(untitled) (Palíndromo, 2021)
“End of Time in the hearts, isolated” is a visual essay composed of text and 08 images made during the global pandemic covid-19 in social isolation. The paintings and drawings were inspired by existential themes that are widely discussed in the philosophy of Friedrich Nietzsche, and here they gain significance as a reason and importance of making art - for themselves and for everyone, especially in adverse times.